Synthesis and Characterization of Secondary Nitrosamines from Secondary Amines Using Sodium Nitrite and p‐Toluenesulfonic Acid. Issue 3 (12th January 2015) - Miró Sabaté, Carles; Delalu, Henri
Abstract We synthesized nitrosamines (R2NNO) with R=iPr (1), nPr (2), nBu (3), and hydroxyethyl (4) from the amine using sodium nitrite/p‐toluenesulfonic acid in CH2Cl2. The rate of formation of 1–4 increases in the direction iPr<nPr<nBu<CH2CH2OH. Compounds 1–3 were obtained as colorless solids, whereas 4 is a bright yellow liquid. Compounds 1–4 were characterized by elemental analysis, MS, IR, and multinuclear NMR (1H, 13C, and 15N) spectroscopies. Additionally, we measured the UV/Vis spectra of all compounds, which show maxima of absorption at approximately 221 nm and molar extinction coefficients between 3043 and 4859 L mol−1 cm−1. We calculated the optimized structures of 1–4 (B3LYP/6‐311+G(d, p)) and computed the NMR spectroscopic chemical shifts and infrared frequencies. Furthermore, we carried out a natural bond orbital (NBO) analysis of the nitrosamine moiety. Lastly, the compounds described in this work are valuable starting materials for the synthesis of 2‐tetrazenes with potential interest to replace highly toxic hydrazines in rocket propulsion.